Hubungan Indeks dmf-t Dengan Status Sosiodemografi Orang Tua Pada Anak Usia 4-5 Tahun di TKN Kota Bandung - Resti Pratita; Linda Sari Sembiring; Grace Monica (Maranatha Christian University, 2019)
Dental and oral health is a part of body’s health that can not be separated from one another. Dental caries is more common in childhood during preschool. Dental health education must be introduced as early as possible to children so they know how to maintain good dental and oral health. Children aged 4?5 years need help from their parents in brushing their teeth. Parents play an important role in maintaining oral health. Sociodemographic factors may affect oral health, such as family income and education. The purpose of this study was to determine the relationship of the dmf-t index in children aged 4?5 years in kindergartens in Bandung with the sociodemographic status of parents. This study is an analytical study using a cross sectional approach. This research was conducted by survey method and the number of samples used the whole sampling method. Examination of caries severity using dmf-t index and parents filled out the questionnaire. The statistical analysis used in this study was multivariate analysis. From the results of the average dmf-t score in kindergarten students, which numbered 80 childrens are in the high category (5.86) and father's education has a significant relationship with the child's dmf- t index. The conclusion of this study is that there is no relationship between the dmf-t index of children aged 4?5 years in kindergartens in Bandung with the sociodemographic status of parents.